The Portuguese NHS 2024 reform - Goiana-da-Silva, Francisco (2024)
Funding Information: The author(s) declare financial support was received for the research, authorship, and/or publication of this article. After submission, Imperial College London kindly agreed to fund the open access fees for this paper. Publisher Copyright: Copyright © 2024 Goiana-da-Silva, Sá, Cabral, Guedes, Vasconcelos, Sarmento, Morais Nunes, Moreira, Miraldo, Ashrafian, Darzi and Araújo.